Direct and facile synthesis of highly porous low cost carbon from potassium-rich wine stone and their application for high-performance removal - Arslanoglu, Hasan (Elsevier, 2019)
Alkaline potassium compounds such as K2CO3 and KOH are chemical activators used to produce activated carbons (ACs). The substance, known as wine stone or cream of tartar and formed in wine fermentation tanks during wine production from grape juice concentrates, consists of potassium hydrogen tartrate (KHC4H4O6). Highly porous carbons with various textural characteristics were obtained from organic wine stone subjected to simple heat-treatment. This procedure is a one-step carbonization treatment performed at different carbonization temperatures (400 and 900 degrees C) and times (15 and 360 min), and nitrogen flow rates (100 and 600 ml/min). The chemical and physical properties of AC were examined using SEM-EDX, FT-IR analysis, particle size distribution, iodine number, pHpzc, BET surface area, surface functional group analysis by the Boehm's titration. BET surface area, total pore volume, average pore diameter, iodine number, pHzpc and carbon content were 1814.6 m(2) g(-1), 0.7767 cm(3) g(-1), 18.2 angstrom, 1986.4 mg g(-1), 6.18 and 92.96%, respectively. Pore size, surface area and pore volume increased with an increase in carbonization temperature, and AC surface had high porosity and acidic functional groups. A promising approach focusing on the use of potassium-enriched properties of wine stone for easy and environmentally friendly production of activated carbons is emphasized.
Keywords: Activated carbon; Porous carbons; Wine stone; Potassium hydrogen tartrate; Cream tartrate